Konsep Subyek Hukum Dalam Hukum Islam, Hukum Positif dan Kompilasi Hukum Ekonomi Syariah - Ahmad Badrut Tamam (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2018)
Indonesia is a legal state that recognizes everyone as a human being against laws which means that everyone is recognized as a legal subject. Long before the law, provisions regarding humans as legal subjects were regulated in Islamic law, which is called mahkūm ‘alaih. The term legal subject continues to grow with the existence of legal subjects other than people, namely legal entities. Development The term legal entity in Indonesia goes hand in hand with the ratification of several Islamic laws and regulations, such as the law on waqf, the law on zakat, the law on the Religious Court, and the Compilation of Syariah Economic Law (KHES). This paper intends to describe the differences and similarities in the concept of legal subjects in Islamic law, positive law and the compilation of Shari'ah Economic Law.